A face do feminino na poética de Guilherme de Almeida - Redondo, Altamiro José (2009)
The object of this thesis is the Guilherme de Almeida`s love poetry, which shows universal elements whose basis is archetypical and mythological. It still has the intention of contributing to the poet`s critical fortune, which has been contemplated insufficiently until now. In his poems, the woman is not represented physically, but is changed into a constant fleeting image, which is confounded with the own concept of love or feminine principle. It is chosen to exalt the love from the past or from the future, and the woman from the present is sung in her abstraction. By meeting these images, the androgyny myth shows a welcoming answer. This myth, unlike the imaginary distant idea that it has about, is very modern and involves a psychological reality behind the whole love search, apart from meaning a cosmic fullness condition metaphor in which the opposites are confounded. Other myths based on the androgyny figure are also contemplated. The relationship between the poetic corpus and the androgyny myth is made by the comparison and the similarity of their images, apart from analyses and deductions. For that relationship, especially Mircea Eliade contributes, among others, to his ideas about the reproduction of images, according to Images and Symbols (1991). The search for the love fullness, to which the myth refers to, occurs, therefore, in the poetic textual body, in which the woman is sublimated and represents the own lost self for good. As a consequence, the search for this fullness experience also has an initiatory and spiritual nature. It seeks to identify the concept of love in its poetry through the comparison with other similar concepts, such as the passion love, the sublime love, and the erotic love. It still develops an introductory study of Guilherme de Almeida`s work in general focusing on its literary characteristics and its qualities according to the criticism, highlighting the question of the engagement with the sublime universal aspect, as well as pointing out especially the symbolist tones of his poetry that, returned to ethereal fleeting spiritual images, keep an intimate relationship to his love poems and to the subject of his thesis